Glucose restriction induces transient G2 cell cycle arrest extending cellular chronological lifespan - Masuda, Fumie (Sci Rep, 2016)
While glucose is the fundamental source of energy in most eukaryotes, it is not always abundantly available in natural environments, including within the human body. Eukaryotic cells are therefore thought to possess adaptive mechanisms to survive glucose-limited conditions, which remain unclear. Here, we report a novel mechanism regulating cell cycle progression in response to abrupt changes in extracellular glucose concentration. Upon reduction of glucose in the medium, wild-type fission yeast cells undergo transient arrest specifically at G2 phase. This cell cycle arrest is dependent on the Wee1 tyrosine kinase inhibiting the key cell cycle regulator, CDK1/Cdc2. Mutant cells lacking Wee1 are not arrested at G2 upon glucose limitation and lose viability faster than the wild-type cells under glucose-depleted quiescent conditions, suggesting that this cell cycle arrest is required for extension of chronological lifespan. Our findings indicate the presence of a novel cell cycle checkpoint monitoring glucose availability, which may be a good molecular target for cancer therapy.